2018
DOI: 10.3390/nu10040488
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis

Abstract: Flavonoids have been implicated in the prevention of cardiovascular diseases (CVD). In a prospective approach, we investigated whether habitual flavonoid intake from fruit, vegetables and juices (FlavFVJ) during adolescence is associated with adult levels of serum lipids, one of the main CVD risk factors. This analysis included healthy participants from the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study, who had provided a fasting blood sample in adulthood (aged 18–39 years), da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Mean total flavonoid intake for adolescents (12•5-17•5 years) in the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study was estimated at 120 mg/4184 kJ per d using two non-consecutive 24-h recalls (10) . Since dietary habits develop during childhood and adolescence, they are considered very important for shaping lifelong dietary habits and the prevention of chronic diseases later in life (11,12) . However, the few studies that described flavonoid intake in children and adolescents are limited to cross-sectional analysis (7,8) , a certain age group (9) , girls (9) , or in the case of isoflavones to Asian populations (13) .…”
mentioning
confidence: 99%
“…Mean total flavonoid intake for adolescents (12•5-17•5 years) in the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study was estimated at 120 mg/4184 kJ per d using two non-consecutive 24-h recalls (10) . Since dietary habits develop during childhood and adolescence, they are considered very important for shaping lifelong dietary habits and the prevention of chronic diseases later in life (11,12) . However, the few studies that described flavonoid intake in children and adolescents are limited to cross-sectional analysis (7,8) , a certain age group (9) , girls (9) , or in the case of isoflavones to Asian populations (13) .…”
mentioning
confidence: 99%
“…The results of the previous observational studies about the association between total flavonoid intake from foods and HDL-cholesterol were inconsistent. In the follow-up study with German, total flavonoid intake from fruit, vegetables, and juices during adolescence was associated with higher HDL-cholesterol levels only in men, not in women [34]. Cross-sectional studies of Iranians, Italians and Americans showed positive relationships between total flavonoid intakes and HDL-cholesterol levels [35][36][37], but no correlation was observed in studies with Chinese and Polish [38,39].…”
Section: Discussionmentioning
confidence: 82%
“…There are many large population studies that demonstrated the inverse associations between fruit and vegetable consumption with adiposity, BMI, or waist circumference. 26 27 28 Also, there are various data to support the relationship between antioxidant diet and hyperlipidemia 29 30 or hypertension. 31 32 33 Recent meta-analysis on food groups and risk of hypertension showed an inverse association for the risk of hypertension for 100 g of fruits/d (relative risk: 0.97).…”
Section: Discussionmentioning
confidence: 99%